IgG4-related disease presenting as a submucosal tumor of the stomach resected with laparoscopic endoscopic cooperative surgery: a case report - Taishi Yamane; Kojiro Eto; Takeshi Morinaga; Kazuki Matsumura; Kohei Yamashita; Ryuma Tokunaga; Kazuto Harada; Yukiharu Hiyoshi; Yohei Nagai; Masaki Iwatsuki; Shiro Iwagami; Yuji Miyamoto; et al. (Surgical Case Reports, 2020)
Abstract Background IgG4-related disease (IgG4-RD) is an immune-mediated disorder in which abundant IgG4-positive plasma cells infiltrate affected organs. There have been reported four cases of probable IgG4-RD presenting as a submucosal tumor of the stomach. We herein report the first case of definite IgG4-RD presenting as a submucosal tumor of the stomach resected with laparoscopic endoscopic cooperative surgery (LECS). Case presentation A 70-year-old woman with a 6-year history of autoimmune pancreatitis was referred to our department because a 15-mm submucosal tumor in the greater curvature of the lower part of the stomach had been identified via upper gastrointestinal endoscopy. Endoscopic ultrasonography showed a 10-mm low-echoic lesion derived from the submucosal layer of the stomach. A fine-needle aspiration biopsy was attempted, but the tumor was too hard for sampling. F-fluorodeoxyglucose (FDG) positron emission tomography showed an FDG uptake, suggesting a possibility of malignant disease. As the diagnosis could not be confirmed, LECS for both the diagnosis and curative treatment was performed. A histopathological examination showed a tumor with IgG4-positive lymphoplasmacytic infiltration and fibrosis. The ratio of IgG4+/IgG+ lymphoplasmacytic cells was > 80%. A laboratory examination showed elevation of the serum IgG4 levels preoperatively. Thus, the final diagnosis was IgG4-RD of the stomach. No recurrence was observed within 1 year after surgery. Conclusions We encountered a case of definite IgG4-RD presenting as a gastric SMT in which a correct diagnosis was achieved by a minimally invasive LECS technique. IgG4-RD may present as a gastric lesion and should be taken into consideration as a differential diagnosis.